2015
DOI: 10.1016/j.jpainsymman.2014.11.298
|View full text |Cite
|
Sign up to set email alerts
|

The Refusal of Palliative Radiation in Metastatic Non-Small Cell Lung Cancer and Its Prognostic Implications

Abstract: Patients with metastatic NSCLC who refuse recommended palliative radiation have a poor survival. Radiation refusal or the recommendation against treatment can serve as a trigger for integrating palliative care services sooner and contributes greatly to prognostic awareness. Further investigation into this survival difference and the factors behind refusal are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 36 publications
0
28
0
2
Order By: Relevance
“…18,19 In the US, 3% of patients, primarily elderly, non-black/non-white, and unmarried female patients refuse palliative radiation for metastatic NSCLC. 28 In our study, the mean age difference between the TG and NTG was nine years. Lung cancer occurs mainly in elderly patients and mortality increases with age, 29 particularly in Asian and Caucasian populations.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…18,19 In the US, 3% of patients, primarily elderly, non-black/non-white, and unmarried female patients refuse palliative radiation for metastatic NSCLC. 28 In our study, the mean age difference between the TG and NTG was nine years. Lung cancer occurs mainly in elderly patients and mortality increases with age, 29 particularly in Asian and Caucasian populations.…”
Section: Discussionmentioning
confidence: 46%
“…In colorectal cancer patients, the treatment refusal group was on average 4.6 years older than the treated group . In the US, 3% of patients, primarily elderly, non‐black/non‐white, and unmarried female patients refuse palliative radiation for metastatic NSCLC . In our study, the mean age difference between the TG and NTG was nine years.…”
Section: Discussionmentioning
confidence: 56%
“…Controlling the primary tumor was found to prolong patient survival and may lead to long‐term survival of patients with stage IV NSCLC . Refusing palliative RT led to poor survival . Both the 2011 American Society for Radiation Oncology (ASTRO) Guideline and the 2014 European Society for Medical Oncology (ESMO) Guideline concluded that RT plays a major role in controlling the symptoms of metastases, such as painful chest wall disease, superior vena cava syndrome, soft tissue, or neural invasion.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Refusing palliative RT led to poor survival. 36 Both the 2011 American Society for Radiation Oncology (ASTRO) Guideline and the 2014 European Society for Medical Oncology (ESMO) Guideline concluded that RT plays a major role in controlling the symptoms of metastases, such as painful chest wall disease, superior vena cava syndrome, soft tissue, or neural invasion. Therefore, there is no doubt that palliative TRT plays an important role in metastatic lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Stereotactic body radiotherapy (SBRT) has been shown to be safe and efficacious in patients with oligometastatic lung cancer in a variety of additional anatomic locations (8,(24)(25)(26). Further, a previous study of the SEER database showed that patients refusing palliative RT for metastatic NSCLC had diminished OS relative to those not refusing RT (27).…”
Section: Discussionmentioning
confidence: 99%